Protective IgM-mediated immunity against Vibrio anguillarum in Atlantic cod with evolutionary losses of mhc class II and cd4 - Jonsson, Alexandra; López-Porras, Adrián; Nørstebø, Simen Foyn; Guslund, Naomi Croft; Sørum, Henning; Qiao, Shuo-Wang; Johansen, Finn-Eirik (Frontiers in Immunology, 2025)
The unique adaptive immune system of the Atlantic cod (Gadus morhua), with genetic loss of the mhc class II and cd4, poses questions about the protective role of specific antibodies in this species. We investigate the IgM response against Vibrio anguillarum, a common pathogen in aquaculture. Juvenile Atlantic cod were bath-immunized with formalin-fixed V. anguillarum serotype O2a. Vaccinated cod were fully protected against lethal vibriosis when challenged by immersion with serotype O2a and partially protected against challenge with serotype O2b. Serum IgM from immunized cod reacted specifically with V. anguillarum O2a in ELISA, with some crossreactivity towards the O2b serotype. Bath-immunized cod were also protected against intracelomic challenge with V. anguillarum O2a, supporting the induction of systemic immunity by bath vaccination. Passive transfer experiments were conducted to evaluate the protective efficacy of IgM. Naive cod that received total serum or purified IgM from immunized donors were protected against lethal vibriosis; whereas, naive cod that received naive serum were not protected. Western blotting revealed that these protective antibodies recognized a proteinase K-sensitive antigen rather than lipopolysaccharides. These insights enhance our understanding of cod immunity and provide guidance for developing future vaccination strategies in aquaculture.